Theoretical and methodological approaches to periodization of technical and technological development - Dubey, Yuliya (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The article is devoted to the problem of technical and technological development, which in the modern globalized world is subject to the laws of cyclicity. The realities of today are evidence that in every country of the world coexist and interact elements of different levels of technological structures, which requires a balanced policy to manage their development. Therefore, the purpose of this study is to identify the main theoretical and methodological approaches to the periodization of technical and technological development of the world economy and the formation of generalized criteria for structuring periods of its cyclical dynamics. In the course of the research the tasks were solved, which consisted in the selection of those theoretical and methodological approaches that most fully cover the causal links between changes in technology and technology, on the one hand, and development – on the other; identifying in each approach the criteria of periodization and determining the possibilities of these approaches to describe the current situation. The methodological basis was such general scientific research methods as dialectics, analysis and synthesis, the unity of historical and logical, as well as methods of generalizations, comparisons and classifications. The result of their application was to clarify the essence and establish the specifics of the conceptual approaches of M. Kondratiev, С. Perez and S. Glazyev, which today are considered to be leading in explaining technical and technological development. Based on the comparison of these theoretical and methodological approaches, a generalized idea of the criteria for periodization of the latter is formed. The general conclusion of the study is the formation of scientific ideas about the stages through which society passes in its technical and technological development. This allows you to properly assess the current state of a particular economic system and choose more effective instruments of economic policy to guide its development through progress.